Arthropod Communities On Sonneratia Caseolaris Along Selangor River, Kampung Kuantan, Kuala Selangor, Malaysia - Nurul Aina Adnan; Mamat Nur-Syahirah; Dzulhelmi Muhammad Nasir; Nur-Athirah Abdullah; Lailatul-Nadhirah Asri; Muhammad Faiz Zakaria; Adnan Amin-Safwan; Surzanne Mohd Agos; Wan Juliana Wan Ahmad; Maimon Abdullah; Norela Sulaiman; Faszly Rahim (UNIMAS Publisher, 2024)
Indexed by Scopus/MyCite